Peran Manajer Dalam Meningkatkan Kinerja Karyawan - Tiara Lubis; Muhammad Wafi Siregar; Ulfa Hayana Sari Harahap; Tengku Darmansah (Jurnal Bisnis Kreatif dan Inovatif, 2024)
This literature research aims to compile and describe the role of managers in improving employee performance. The method used is the library research method. The data collection method used is the documentation method. The data analysis technique used is content analysis. To maintain the accuracy of the assessment and prevent errors in information in data analysis, cross-library checks are carried out and re-reading the literature and paying attention to the reviewer's comments. The results of this study show that the better the motivation provided by managers, the more significant it can improve employee performance.